Caregivers’ resilience is independent from the clinical symptoms of dementia - Rachel Dias; José Pedro Simões-Neto; Raquel Luiza Santos; Maria Fernanda Barroso de Sousa; Maria Alice Tourinho Baptista; Isabel Barbeito Lacerda; Nathalia Ramos Santos Kimura; Marcia Cristina Nascimento Dourado (Arquivos de Neuro-Psiquiatria)
ABSTRACT Resilience is the capacity for successful adaptation when faced with the stress of adversity. We aimed to investigate the relationship between caregivers’ resilience and the sociodemographic and clinical factors of people with dementia. Cross-sectional assessment of 58 people with dementia and their caregiver dyads showed that most caregivers were female adult children. The caregivers reported moderate to higher levels of resilience, lower levels of anxiety and depressive symptoms and moderate levels of burden. Resilience was not related to the caregiver’s gender (p = 0.883), nor clinical (p = 0.807) or emotional problems (p = 0.420). The regression showed that resilience was related to the caregiver’s quality of life (p < 0.01) and inversely associated with their depressive symptoms (p < 0.01). There was no relationship between caregivers’ resilience and the sociodemographic and clinical characteristics of people with dementia. We can assume that resilience is an individual characteristic. Support groups should also focus on the factors that may increase resilience among caregivers.